Nanomaterials for food applications - Amparo, Lopez Rubio; Rovira, Maria Jose; Sanz, Marta Matinez; Gomez-Mascaraque, Laura Gomez (Micro & nano technologies., 2019)
Nanomaterials for Food Applications highlights recent developments in nanotechnologies, covering the different food areas where these novel products or technologies can be applied. The book covers five major themes, showing how nanotechnology is used in food, the use of ingredients in nanoform to improve bioavailability or nanoencapsulation technologies, nanotechnologies for food processing, nanosensors for food quality and safety, nanotechnologies for food packaging, and methods to evaluate potential risks and regulatory issues. This is an important research reference that will be of great value to academic and industrial readers, as topics of importance, both at a research level and for commercial applications, are covered. Regulatory agencies will also be interested in the latest developments covered in the book as they will help set the foundation for further regulations.